Gender-specific dynamics in working hours - Inge Noback; Lourens Broersma; Jouke van Dijk (European Regional Science Association (ERSA), 2011)
Gender-specific dynamics in working hours ERSA Barcelona 2011 The Dutch are part-time working champions of the world, not just because the majority of women work part-time, also a growing number of men are working part-time. However, with the aging of the population there is an increasing threat to current welfare levels. The aim of this paper is to assess the possibilities of a rise in wealth through a change in (the trend of) working hours. For the analysis we have created a unique data base which includes workers that have occupied the same job in the period 2003-2005. This means we abstain from dynamics in jobs, (i.e. job finders, job switchers, job losers), which can partly be attributed to changes in participation. Instead we focus completely at working hours of a given job. The analysis is comprised of two parts, first we analyse factors determine the actual number of hours worked for both female and male occupied jobs. Second, we analyse the dynamics in working hours of a given job using a bivariate probit estimation with selection. This model takes into account what factors determine if a person does or does not change working hours and subsequently examines which factors determine whether this change is an increase or a decrease in working hours. Women more frequently change their working hours than men and both rather decrease than increase their working hours. Changes in work situation and household situation are important determinants of changes in working hours, for women also changes in residential context play a role. A decrease in hourly wage and a relative decrease in the burden of taking care of small children are important determinants of increasing working hours, for both men and women. Although men only decrease their working hours after the birth of the first child.
Keywords: 330